2017
DOI: 10.1111/hel.12380
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world practice and Expectation of Asia‐Pacific physicians and patients in Helicobacter Pylori eradication (REAP‐HP Survey)

Abstract: It is time for physicians in Asia-Pacific countries to adopt newer and more efficacious anti-H. pylori regimens to meet the Kyoto consensus recommendation and their patients' expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…A real-world study indicated that the expectation of eradication rate was over 90% by patients and about 86% by physicians. 33 Apparently, clinical practice neither satisfied public expectations nor met physicians' needs.…”
Section: Discussionmentioning
confidence: 99%
“…A real-world study indicated that the expectation of eradication rate was over 90% by patients and about 86% by physicians. 33 Apparently, clinical practice neither satisfied public expectations nor met physicians' needs.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire encompassed eight questions focusing on following categories: age, gender, specialty, location of medical practice, types of hospital, most commonly prescribed regimen, factor that causes the most concern when prescribing first line anti-H. pylori regimen (eradication rate, side effect, cost, number of pills, duration of regimen, convenience, and other factors), and the accepted minimal eradication rate of a first-line anti-H. pylori regimen (≥95%, ≥90%, ≥85%, ≥80%, ≥75%, ≥70%, ≥65%, ≥60%, and others). 18 The mean accepted minimal eradication rate of gastroenterologists was defined as the mean value of accepted minimal eradication rates chosen by the…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, we distributed the same questionnaire to the Taiwanese gastroenterologist who attended the Asia-Pacific Digestive Week 2015, and the Survey results had been reported. 18 In the current study, we compared the survey data between Taiwanese gastroenterologists in 2020 and those surveyed in 2015.…”
Section: Differences In H Pylori Treatment Survey Data Between Gastro...mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A recent survey for H. pylori eradication therapy revealed that 7-day standard triple therapy remained the most popular regimen in the Asia-Pacific region. 5 Most physicians in Taiwan, Japan, and Korea adopted 7-day and 14-day standard triple therapies in the first-line treatment of H. pylori infection (62% and 21%, 100% and 0%, and 81% and 7%, respectively). However, the prevalence of antibiotic resistance markedly increases with time worldwide, and the eradication rate of standard triple therapy has decreased to less than 80% in most countries worldwide.…”
mentioning
confidence: 99%